Pendidikan agama berwawasan multikultural - Baidhawy, Zakiyuddin (Ciracas, Jakarta : Erlangga, 2005)
Multicultural approach to religious education in Indonesia
Daftar pustaka : p. 129-133
Keywords: Religious education -- Indonesia; Multicultural education -- Indonesia